ANALISA HUBUNG SINGKAT PADA PLTMG AMBON PEAKER 30 MW - Aryo Nugroho, Teguh; Hamles Latupeirissa; Arnold Kastanya (Politeknik Negeri Ambon, 2025)
With the increasing demand for electricity in Indonesia, both industrial and household, a reliable electrical system is required. One of the electrical system faults, such as a short-circuit fault in a generator, can disrupt electricity delivery and cause damage to equipment. This research concentrates on analyzing short circuit faults in the Ambon Peaker Gas Oil Power Plant (PLTMG), which has four generator units with a capacity of 30 MW. The main objective of this study is to determine how much short-circuit fault current occurs during three-phase, phase-phase, and phase-ground faults, as well as the components that affect these currents. Data collection on power system characteristics and the use of ETAP (Electrical Transient Analysis Program) software were used. The results showed that there was a short-circuit current fault at bus 1 of the Ambon MHP with a three-phase fault of 14.727 kA, a ground-phase fault of 15.998 kA, and a phase-phase fault of 12.926 kA. With these results, this study provides recommendations for the selection of appropriate protection equipment to minimize losses due to disturbances in the power system at the Ambon Peaker MHP. Keyword : Short circuit fault, PLTMG, ETAP